(untitled) (International journal of artificial intelligence, 2024)
This article discusses the ongoing information attacks in the world, the global arms trade, ideological threats, and their negative impacts on society, particularly on the upbringing of the youth. It also addresses the fight against harmful ideologies being spread under the guise of democracy and human rights. The article emphasizes the importance of developing genuine ideological immunity in the minds and consciousness of the youth of Uzbekistan against these ideological threats.